To solve the system of equations:
y = -2x - 1
3x - y = -7
We can start by substituting the value of y from the first equation into the second equation:
3x - (-2x - 1) = -7
Simplifying:
3x + 2x + 1 = -7
Combining like terms:
5x + 1 = -7
Subtracting 1 from both sides:
5x = -8
Dividing both sides by 5:
x = -8/5
Now, we can substitute this value of x back into the first equation to find y:
y = -2(-8/5) - 1
y = 16/5 - 1
y = 16/5 - 5/5
y = 11/5
So, the solution to the system of equations is x = -8/5 and y = 11/5.
y=−2x−1%0D%0A%0D%0A=%0D%0A−%0D%0A2%0D%0A%0D%0A−%0D%0A1%0D%0A %0D%0A3x − y =−7
3 answers
what is the (,)?
In this case, the (,) is used to separate the x and y values in the solution to the system of equations. For example, the solution is written as (x, y) = (-1.6, 2.2), indicating that the value of x is -1.6 and the value of y is 2.2.